CFD-based design of air wall water blocking for underground garage entrances and exits - Li Bin; Jiang Feng; Yan Lan; Jiang Anna (PLoS ONE, 2025)
In the increasingly perfect underground garage construction process, the underground garage entrance water blocking problem is getting more and more attention. This paper proposes a kind of air wall water-blocking device applied to underground garage. The device is installed on the side of the straight and curved paths at the entrances and exits of the spiral underground garage. It utilizes two fans to blow the water to the drain on the other side to achieve unobstructed access to stop the water. In this paper, CFD simulation is firstly carried out on the straight road of the spiral underground garage to verify the feasibility of the program. The accuracy of the simulation results was verified by building a straight road model and conducting experiments. After that, an equal-scale 3D model of the spiral underground garage was built. Orthogonal experiments on the effects of inlet water flow velocity, fan wind speed at the straight road and fan wind speed at the curved road on the water blocking effect were carried out by using CFD simulation. A preliminary range of water velocity of 2.250 m/min to 6.786 m/min was obtained experimentally, and this range of water velocity was used as an input parameter for the simulation. The results show that the speed of water flow at the entrance of the garage and the wind speed of the fan at the straight road have a greater effect on the water blocking effect than the wind speed of the fan at the curved road. When the wind speed of the fan at the straight road is 25m/s, proper adjustment of the wind speed of the fan at the curved road can realize a good water-blocking effect of the spiral underground garage entrance within the range of water flow rate of 2.250m/min ~ 6.786m/min. Therefore, in the practical application of using the air wall water blocking scheme to realize the underground garage entrance water blocking strategy is to give priority to improve the wind speed of the fan at the straight road to improve the effect of water blocking.